Infratech Value Drivers - World Bank (World Bank, Washington, DC, 2020)
The 2020 G20 Presidency mandated the Infrastructure Working Group (IWG) to develop an agenda to accelerate the adoption and application of technology-enabled infrastructure (InfraTech). This agenda supports two existing IWG initiatives, the Roadmap to Infrastructure as an Asset Class, and the G20 Principles for Quality Infrastructure Investment (QII). Technology supports the roadmap by providing enhanced data, tools, and transparency for investors. In addition, it creates new investment opportunities by creating new markets, business models and potential for enhanced revenues. InfraTech also supports QII, as many technologies maximize the positive impact of infrastructure by enhancing sustainability, inclusivity, and resilience. The potential economic efficiencies that new technologies offer also help attain value for money across the project lifecycle and potentially reduce upfront or recurring public financial outlays. InfraTech also provides valuable tools for governments to respond to the COVID-19 health and economic crisis. This Reference Note supports the InfraTech Agenda endorsed by the G20 Infrastructure Working Group by outlining the potential economic, social, and environmental value to countries generated by adopting InfraTech solutions. It also provides a framework for evaluating the benefits of these solutions against their costs and risks. This paper focuses on the transport, energy, water, and digital infrastructure sectors.